2019
DOI: 10.3390/ani9040138
|View full text |Cite
|
Sign up to set email alerts
|

The Views of the UK Public Towards Routine Neutering of Dogs and Cats

Abstract: Despite being routinely recommended by veterinarians, neutering of dogs and cats has both positive and negative impacts on animal welfare and is ethically problematic. We examined attitudes of a sample of the UK public towards routine neutering of dogs and cats using a questionnaire. Respondents indicated their level of agreement with statements describing welfare and ethical reasons ‘for’ and ‘against’ the neutering of male and female dogs and cats. We conducted a general linear model (GLM) analysis to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…We wanted to better understand how dog owners' decisions to desex their dogs are influenced by professional advice and the common beliefs about the behavioural consequences. This is especially important as presently prospective causal data in this area are missing [5,6], but individually based advice is recommended in areas where population management does not apply [6,31]. Consequently, advising professionals such as veterinarian practitioners, behavioural trainers and behavioural therapists could benefit from information on how dog owners decide to castrate their male dog or not.…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to better understand how dog owners' decisions to desex their dogs are influenced by professional advice and the common beliefs about the behavioural consequences. This is especially important as presently prospective causal data in this area are missing [5,6], but individually based advice is recommended in areas where population management does not apply [6,31]. Consequently, advising professionals such as veterinarian practitioners, behavioural trainers and behavioural therapists could benefit from information on how dog owners decide to castrate their male dog or not.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical methods are the most widely used form of desexing in dogs, and are the most commonly performed surgeries in the species overall [7,10,[13][14][15][16]. They can be differentiated into surgeries that remove the gonads (orchiectomy, ovariectomy, ovariohysterectomy) and surgeries that do not (vasectomy, salpingectomy, hysterectomy), the former methods being considerably more common than the latter.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…Desexing is somewhat less common in anglophone Western Europe, with prevalences reaching 54% in the UK [3] and 47% in Ireland [4]. In contrast, desexing is considered illegal without a clear medical indication in Germany [5] as well as some of the Nordic countries [6][7][8], with prevalences below 10% in Sweden [9].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, some participants’ responses suggest that experience with castration in pets may contribute to castration of animals being somewhat normalized. A survey in the UK found that citizens were predominantly supportive of dog and cat neutering [ 76 ]. Dog owners in The Netherlands said that correcting unwanted behaviors was an important reason to have their male dogs neutered [ 77 ], supporting that perception of necessity may lead to support of the practice.…”
Section: Discussionmentioning
confidence: 99%